1998
DOI: 10.1093/ajcn/67.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the flavonoids quercetin and apigenin on hemostasis in healthy volunteers: results from an in vitro and a dietary supplement study

Abstract: Intake of dietary flavonols and flavones was inversely associated with risk for cardiovascular disease in several epidemiologic studies. This may have been due to effects on hemostasis because flavonoids have been reported to inhibit platelet aggregation in vitro. We indeed found that 2500 micromol/L of the flavonol quercetin and the flavone apigenin significantly inhibited collagen- and ADP-induced aggregation in platelet-rich plasma and washed platelets by approximately 80-97%. However, lower concentrations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
152
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(163 citation statements)
references
References 33 publications
9
152
1
1
Order By: Relevance
“…This may re¯ect the signi®cantly higher¯avo-noid concentrations used in in vitro studies (10 ± 50 mM; Mower et al, 1984) compared with those achieved following 6 weeks' rutin supplementation (mean plasma quercetin concentration 0.14 + 0.03 mmolal plasma). It therefore appears that the concentrations of¯avonoids necessary for anti-aggregatory activity in vitro have not been attained in vivo by rutin supplementation at the recommended dose or by dietary intake as previously demonstrated by Janssen et al (1998).…”
Section: Discussionmentioning
confidence: 83%
“…This may re¯ect the signi®cantly higher¯avo-noid concentrations used in in vitro studies (10 ± 50 mM; Mower et al, 1984) compared with those achieved following 6 weeks' rutin supplementation (mean plasma quercetin concentration 0.14 + 0.03 mmolal plasma). It therefore appears that the concentrations of¯avonoids necessary for anti-aggregatory activity in vitro have not been attained in vivo by rutin supplementation at the recommended dose or by dietary intake as previously demonstrated by Janssen et al (1998).…”
Section: Discussionmentioning
confidence: 83%
“…Previous intervention studies have shown that distinctive components of MD reduce platelet function, and this effect has been proposed as a mechanism contributing to the CV benefit of this diet. In fact, fish oils (Goodnight et al, 1981;Agren et al, 1997;Vognild et al, 1998), a-linolenic acid (Renaud & Nordøy, 1983;Allman et al, 1995;Freese et al, 1994) and various spices (Janssen et al, 1998;Ackerman et al, 2001;Srivastava et al, 1995) induce a decrease of platelet function. The apparent discrepancy of our results with those findings is probably explained by the lower content of each one of these substances in the complete MD, as opposed to the amounts used for single components of MD in selective intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, some of the beneficial effects of MD and wine consumption could be mediated by a reduction in platelet reactivity. Several studies report that diets enriched with fish, a-linolenic acid and spices, abundant in the case of MD, include substances that reduce or could reduce platelet function (Vognild et al, 1998;Allman et al, 1995;Janssen et al, 1998;Ackerman et al, 2001;Srivastava et al, 1995). Similarly, other reports indicate that the intake of moderate amounts of ethanol or nonalcoholic components of wine, for 2 or more weeks, is associated with a decrease in ex vivo platelet function (Pikkar et al, 1987;Pellegrini et al, 1996;Pace-Asciak et al, 1996;Freedman et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Janssen and colleagues recently studied the effects of the¯avonoids quercetin and apigenin (from onions and parsley) on haemostasis in healthy volunteers (Jansen et al, 1998). These polyphenols belong to different classes of¯avonoids (¯avonols and¯avones, respectively), but they also did not affect ®brinogen, PAI-1 activity, factor VII coagulant activity, plasminogen, platelet aggregation or thromboxane B2 production.…”
Section: Effect Of Tea Consumption On In¯ammation and Haemostasis Varmentioning
confidence: 99%